2016
DOI: 10.2522/ptj.20150401
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Rehabilitation Interventions to Improve Gait Speed in Children With Cerebral Palsy: Systematic Review and Meta-analysis

Abstract: Gait training was the most effective intervention in improving gait speed for ambulatory children with CP. Strength training, even if properly dosed, was not shown to be effective in improving gait speed. Velocity training, electromyographic biofeedback training, and whole-body vibration were effective in improving gait speed in individual studies and warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
122
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 53 publications
0
122
0
10
Order By: Relevance
“…A recent systematic review of interventions for children with CP aimed to improve gait speed demonstrated that gait training was the most effective in increasing gait speed with resistance training not shown to be effective, with the exception of high velocity (power) training 38 . Given the task specificity of gait training, this finding is not entirely surprising.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of interventions for children with CP aimed to improve gait speed demonstrated that gait training was the most effective in increasing gait speed with resistance training not shown to be effective, with the exception of high velocity (power) training 38 . Given the task specificity of gait training, this finding is not entirely surprising.…”
Section: Discussionmentioning
confidence: 99%
“…64 Studies with locomotion training that occurred at a frequency of at least twice a week, for 30 minutes, for greater than 9 weeks had the largest effect sizes. 64 Results of several studies report changes at the level of body structures and function, including improved endurance, 9497 reduced ankle stiffness, 97 , increased H-reflex latency, 98 and improved gait kinematics. 99 One investigation used coherence of EMG analysis as a way of measuring and detecting changes in the output of the motor cortex and its transmission to the spinal cord through the corticospinal tract during functional muscle activation.…”
Section: Coupling Timing and Dosementioning
confidence: 97%
“…62, 63 Despite moderate increases in strength, there is no evidence to support that resistance training improves walking speed 64 or changes in gross motor function. 65 One study demonstrates resistance and velocity training both increase strength, but only velocity training produced positive changes in muscle architecture and gait speed.…”
Section: Coupling Timing and Dosementioning
confidence: 99%
See 2 more Smart Citations